2018
DOI: 10.1016/j.jgeb.2018.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Statistical optimization of crude oil bio-degradation by a local marine bacterium isolate Pseudomonas sp. sp48

Abstract: Pseudomonas sp. sp48, a marine bacterium isolated from Bahary area (Alexandria, Egypt), showed a high potency for oil degradation up to 1.5%. Additionally, it showed an ability to consume aromatic hydrocarbons (phenol & naphthalene) and aliphatic (pentadecane) reaching to 79; 73; 62%, respectively. In the current study, Plackett-Burman factorial design was applied to evaluate culture conditions affecting the degradation potency. Analysis of Plackett-Burman design results revealed that, the most significant var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 28 publications
5
17
0
Order By: Relevance
“…Nutrients availability could also promote cell growth and degradation of crude oil by improving the production of the enzyme. The increase of bacterial growth and oil degradation with the addition of yeast extract (Okeke and Frankenberger, 2003;Mukred et al, 2008;Palanisamy et al, 2014;Farag et al, 2018), peptone (Mukred et al, 2008), and beef extract (Dixit and Pant, 2000) were previously reported. The addition of only yeast extract was shown to accelerate bacterial growth and allowed sufficient crude oil degradation as compared to other nutrients.…”
Section: Discussionmentioning
confidence: 60%
“…Nutrients availability could also promote cell growth and degradation of crude oil by improving the production of the enzyme. The increase of bacterial growth and oil degradation with the addition of yeast extract (Okeke and Frankenberger, 2003;Mukred et al, 2008;Palanisamy et al, 2014;Farag et al, 2018), peptone (Mukred et al, 2008), and beef extract (Dixit and Pant, 2000) were previously reported. The addition of only yeast extract was shown to accelerate bacterial growth and allowed sufficient crude oil degradation as compared to other nutrients.…”
Section: Discussionmentioning
confidence: 60%
“…Spillage of oil into marine and fresh water environment causes an increase in carbon content and a drastic decrease in nitrogen content 23 . It has been reported that the addition of a simple carbon source such as glucose increased the biodegradation rate of total petroleum hydrocarbons (TPH) in contaminated samples 24 . Hence in the present study the growth of identified isolates and the biodegradation of PCO were studied under the presence of trace amounts of glucose and yeast extract.…”
Section: Degradation Of Petroleum Hydrocarbons Of Pco In Sea Water Bymentioning
confidence: 99%
“…Based on the contour plots and response surface curves ( Figure 5(a-f)), the fermentation biomass at different levels of the four factors can be predicted [49]. Each contour ellipse plot represents an infinitive number of combinations of two factors, with the other two factors maintained at their central levels [50]. The maximum predicted value is indicated by the response surface confined in the smallest ellipse in the contour diagram.…”
Section: Optimization By Rsmmentioning
confidence: 99%